Revitalisasi “Image” Masyarakat Terhadap Jamu Sebagai Kearifan Lokal Menuju Level Internasional - Isnaeni Isnaeni; Ariel Dwi Puspitasari; Minarni Purnomo; budiastuti budiastuti; Adi Suroso; Ita Trisnowati (Universitas Negeri Surabaya, 2023)
One of the ancestral heritage that has been used since 1135 M is jamu. People know jamu by several terms, including colonial jamu, by which “jamu gendong”, Nusantara jamu, and millennial jamu are developed. The use of jamu was originally intended to maintain health, both to reduce or eliminate symptoms of illness. The use of jamu, which was initially empirically based, developed into a professionally formulated dosage form after laboratorial and clinical evaluating various active compounds. The problem that develops in the community is the reluctance of the millennial generation to consume jamu, due to its bitter taste and unattractive performance. To revitalize the public image of jamu, various efforts have been made, including socialization, modifying the appearance and taste of jamu so that it is suitable for public interest to the international level. This report provides an overview of training activities for making jamu using simple technology, but which can produce healthy, attractive dishes with distinctive flavors and aromas. The activity is carried out in synergy involving academics, practitioners who are members of the East Java Herbal Medicine Association (GP JAMU JATIM) which was initiated by the East Java Industrial Pharmacy Seminat Association (HISFARIN JATIM). The participants of the activity included the UMKM community, pharmacists, practitioners with the main target being residents of the Technical Implementation Unit for Bina Daksa Social Rehabilitation (UPT RSBD) of the Social Service of Bangil District, Pasuruan Regency.